E-LKPD CULTURALLY RESPONSIVE TEACHING DENGAN LIVEWORKSHEETS DAN WAYGROUND PAPER MODE UNTUK MENINGKATKAN HASIL BELAJAR TRIGONOMETRI - Hermawan, Lendi Ike; Fatqurhohman, Fatqurhohman; Ismiyati, Eny (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study was motivated by the low learning outcomes of students in understanding trigonometry concepts and the difficulties they encountered in connecting these concepts with real-life experiences. One contributing factor is that students struggle to comprehend the relationship between theory and its application in everyday life. In addition, the lack of varied teaching methods and limited use of innovative, interactive worksheets have also posed challenges in trigonometry learning. One potential solution is the use of Liveworksheets, a digital interactive worksheet platform that enables teachers to design worksheets based on the Culturally Responsive Teaching (CRT) approach, making them more relevant to students’ cultural backgrounds. Furthermore, Wayground Paper Mode can serve as an alternative tool for conducting formative assessments flexibly, in both print and digital formats. This study aimed to examine the effectiveness of implementing CRT-based e-Worksheets using Liveworksheets and formative assessments with Wayground Paper Mode in improving students’ learning outcomes in trigonometry. The study was conducted with Class XI-1 students at SMAN Mumbulsari using a classroom action research (CAR) method consisting of two cycles. Each cycle included planning, implementation, observation, and reflection phases to identify improvements in students’ learning outcomes. The results showed that in Cycle I, the average student score was 83,74, while in Cycle II, the average increased to 91,35. This improvement indicates that the use of CRT-based e-Worksheets with Liveworksheets and formative assessments via Wayground Paper Mode effectively helped students gain a better understanding of trigonometry concepts. Moreover, this strategy also proved to enhance students’ motivation and critical thinking skills, as reflected in their increased engagement and academic performance. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar peserta didik dalam memahami konsep trigonometri serta kesulitan yang mereka hadapi dalam menghubungkan konsep tersebut dengan pengalaman nyata. Salah satu faktor penyebabnya adalah peserta didik mengalami kesulitan dalam memahami keterkaitan antara teori dan penerapannya dalam kehidupan sehari-hari. Selain itu, metode pembelajaran yang kurang variatif serta terbatasnya penggunaan LKPD interaktif yang inovatif turut menjadi kendala dalam pembelajaran trigonometri. Salah satu LKPD interaktif digital yang dapat digunakan adalah Liveworksheets, yang memungkinkan guru merancang LKPD berbasis Culturally Responsive Teaching (CRT) agar lebih relevan dengan latar belakang budaya peserta didik. Selain itu, Wayground Paper Mode juga dapat menjadi alternatif dalam melakukan asesmen formatif secara fleksibel, baik dalam bentuk cetak maupun digital. Penelitian ini bertujuan untuk mengetahui efektivitas penerapan e-LKPD berbasis Culturally Responsive Teaching dengan Liveworksheets dan Wayground Paper Mode dalam meningkatkan hasil belajar trigonometri. Penelitian ini dilakukan pada peserta didik kelas XI-1 SMAN Mumbulsari dengan menggunakan metode penelitian tindakan kelas (PTK) yang terdiri dari dua siklus. Setiap siklus mencakup tahapan perencanaan, pelaksanaan, observasi, dan refleksi guna mengidentifikasi peningkatan hasil belajar peserta didik. Hasil penelitian menunjukkan bahwa pada siklus I, rata-rata hasil belajar peserta didik sebesar 83,74, sedangkan pada siklus II, rata-rata nilai meningkat menjadi 91,35. Peningkatan ini menunjukkan bahwa penggunaan e-LKPD berbasis Culturally Responsive Teaching dengan Liveworksheets dan Wayground Paper Mode dapat membantu peserta didik lebih memahami konsep trigonometri dengan lebih baik. Selain itu, strategi ini juga terbukti meningkatkan motivasi dan keterampilan berpikir kritis peserta didik, yang ditunjukkan melalui peningkatan keaktifan serta hasil belajar mereka.